Meningkatkan Ekonomi Masyarakat Dengan Peranan KSPP Syariah BMT Barrah - Dikki Darojat; Deden Sumpena; Fathin Anjani Hilman (Jurusan Pengembangan Masyarakat Islam, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Dj, 2022)
Cooperatives exist as a solution for the welfare of the community. KSPP BMT Barrah is a concrete form of institution that helps in improving the community's economy. The purpose of this study is to determine the program, implementation and impact felt by members or customers who have collaborated with KSPP BMT Barrah, Cimahi City Branch. The method used is descriptive qualitative method, and uses an interpretive paradigm. The research results show that: first, the program provided by KSPP BMT Barrah is specifically for members or customers with the aim of improving the economy. Second, the implementation of cooperation programs carried out by members or customers can be carried out because they use simple procedures. Third, the impact felt by members or customers is different, this happens because in the process of managing business capital it depends on the members or customers themselves in managing, but there are similarities, namely members or customers are greatly helped by collaborating with KSPP BMT Barrah.